Places where famous ophthalmologist Albrecht von Graefe lived and worked in Berlin : Mjesta u kojima je glasoviti oftalmolog Albrecht von Graefe živio i radio u Berlinu - Ivanišević, Milan, liječnik (Array, 2019)
Many things are said and written about famous ophthalmologist Albrecht von Graefe. This work gives detailed description of the places where he lived and practiced ophthalmology in Berlin, because very little was written about it and never in one paper. Von Graefe was born in 1828 in villa Finkenherd in the north-west part of Tiergarten in Berlin. He lived in Behrenstrasse, one of the fashionable streets in Berlin, where he began his ophthalmological practice in 1850. Later, in 1852 he founded a famous private eye clinic in Karlstrasse 46 where he treated numerous eye patients and educated many prominent ophthalmologists and surgeons. Several times he had changed his residence addresses. Among other places, he also stayed in Unter den Linden Avenue and Bellevuestrasse near Potsdamer Platz. In 1868 he became the head of the eye clinic in the Charité Hospital. Since then he lived in a spacious house on Viktoriastrasse until his death in 1870. Although Albrecht von Graefe lived only 42 years, he travelled a lot, but most of his life he spent in the city of Berlin. Graefe made many contributions to ophthalmology being considered the “father of glaucoma” and the nestor of modern ophthalmology.